Chromothripsis and focal copy number alterations determine poor outcome in malignant melanoma - Hirsch, Daniela; Kemmerling, Ralf; Davis, Sean; Camps, Jordi; Meltzer, Paul S.; Ried, Thomas; Gaiser, Timo (Cancer research, 2013)
Genetic changes during tumorigenesis are usually acquired sequentially. However, a recent study showed that in 2% to 3% of all cancers a single catastrophic event, termed chromothripsis, can lead to massive genomic rearrangements confined to one or a few chromosomes. To explore whether the degree of genomic instability and chromothripsis influences prognosis in cancer, we retrospectively applied array-comparative genomic hybridization (aCGH) to 20 malignant melanomas that showed, despite comparable conventional clinical and pathologic parameters, a profoundly different clinical course. We compared 10 patients who died of malignant melanoma 3.7 years (median, range 0.9-7.6 years) after diagnosis with 10 patients who survived malignant melanoma and had a median disease-free survival of 14.8 years (range 12.5-16.7 years; P = 0.00001). We observed a striking association between the degree of chromosomal instability, both numerical and structural, and outcome. Malignant melanomas associated with good prognosis showed only few chromosomal imbalances (mean 1.6 alterations per case), predominantly whole chromosome or chromosome arm gains and losses, whereas malignant melanomas with poor prognosis harbored significantly more chromosomal aberrations (13.9 per case; P = 0.008). Array-based CGH showed that these aberrations were mostly focal events, culminating in two cases in a pattern consistent with the phenomenon of chromothripsis, which was confirmed by paired-end sequencing. This is the first description of chromothripsis in primary malignant melanomas. Our study therefore links focal copy number alterations and chromothripsis with poor outcome in patients with malignant melanomas (P = 0.0002) and provides a genetic approach to predict outcome in malignant melanomas. Cancer Res; 73(5); 1454-60. ©2012 AACR.
Gesehen am 22.12.2021